Using Judicial Actions to Address Corporate Human Rights Abuses: Colombia, 2000–2014 (2017)
In October 2014 a lower court in Medellin (Colombia) convicted more than 20 businessmen and women for illicit association with the paramiliaries and forced displacement of the Afro Colombian communities of Curvarado and Jiguamiando. Among them were managers and former employees of nine oil palm companies, including Urapalma SA. The judge ordered the restitution of the communal lands and financial com pension for the victims. This is one of the first criminal rulings that we know of where firms have been held accountable for their role in the vip lence perpetrated during the internal armed conflict, creating an interest ing precedent for future cases. This is an unexpected outcome in Colombia, based on the particu lar historical, political, social and cultural dynamics, and given what we know from the emerging literature on corporate human rights abuses. It is not difficult to imagine why corporations are involved in human rights abuses in a country like Colombia. y the one hand, the country has an ongoing internal armed conflict, low scores in governance and rule of law indexes, and high levels of corruption. On the other hand, govern ments have adopted several development plans focused on attracting FDI and aiming to increase the country's participation in global markets. It is, however, difficult to imagine that companies (or business people) could be held accountable through criminal proceedings and much less that repara tion for victims would be possible.